Implementasi Peraturan Menteri Pendidikan dan Kebudayaan Nomor 10 Tahun 2020 tentang Program Indonesia Pintar pada SMAN 4 Kisaran Kabupaten Asahan - Mela Dwi Valensia Elvira; Indra Muda; Agung Suharyanto (Universitas Medan Area, 2022)
Program Indonesia Pintar (PIP) is a form of funding from the Ministry of Education and Culture to students aged 6-21 years with criteria for underprivileged students. The phenomenon in this study is that the target of students who get this assistance is not yet precise, and the use of funds is still said to be ineffective because the funds used are outside the objectives of this program. This study aims to determine how the implementation of the Smart Indonesia program at SMAN 4 Kisaran. This study uses a descriptive qualitative method that provides a clear description of the problems studied. Data collection techniques used are observation, interviews, and documentation. The results of this study show that the implementation of the regulation of the minister of education and culture number 10 of 2020 regarding the smart Indonesia program at SMAN 4 Kisaran is quite good in terms of indicators of communication, resources, and bureaucratic structure. Suggestions in this study are the need for firmness from the implementor and should pay attention to the accuracy of the proposals of underprivileged students.Keywords: